(Re)locating photojournalism within a transmedia economy: a case study on the meaning-making process with stories of female Boko Haram survivors. (May 2022) - De La Presa, Lucia; Elvira Ruiz, Paloma
This study explores the representations of female captives and survivors of Boko Haram in what the authors define as a transmedia project formed by an ensemble of interconnected multi-modal/media productions circulated through off- and online spaces, and merging photojournalism and humanitarian markets. The authors draw on semiotic analytical tools in unravelling the process of meaning-making and point to a trend of spectacle renewal in which recycled textual and visual elements function as forms of (self) promotion within the transmedia project. In its response to neoliberal logics of production and circulation of culture, this transmedia project ends up reproducing reductionist portrayals of Boko Horam (ex-)captives and empowering Western producers and consumers through representations that fortify a gendered, neocolonial relationship. This research problematizes the moralistic narratives that support this transmedia economy and proposes alternative modes of sharing and consuming photojournalism stories in order to encourage more critical engagement.